The impact of uric acid on acute coronary syndrome prognosis in elderly patients - Yifan Li; Tiantian Sang; Naqiang Lv; Jinxing Liu; Yingzhen Gu; Xiaorong Han; Wei Zhang; Aimin Dang (Annals of Medicine)
Background Uric acid (UA) plays an important role in cardiovascular diseases, yet its implications in elderly patients remains incompletely understood. This study aimed to explore the impact of UA on the prognosis in advanced-age patients with acute coronary syndrome (ACS).Methods We included 526 patients aged 80 and older who were diagnosed with ACS. The UA levels were measured at admission, and patients were divided into four groups based on quartiles of UA levels. Major adverse cardiovascular events (MACE) during follow-up were recorded.Results The median UA level was 344.09 μmol/L, while the median follow-up duration was 64 months. Kaplan-Meier curves demonstrated a higher cumulative incidence of MACE during long-term follow-up in the Q4 group (Log-rank p < 0.05). Cox regression analysis revealed an independent correlation between UA levels and an increased risk of MACE (HR 1.002, 95%CI 1.000–1.003, p = 0.021). The ROC curve indicated that the optimal UA value for predicting MACE was 324.25 μmol/L. After matching through PSM, the MACE-free survival rate was lower in both hyperuricemia group (UA> 420.00 μmol/L) and high UA group (324.25 μmol/L < UA≤ 420.00 μmol/L) compared to the control group. Both hyperuricemia and high UA levels were independent risk factors for long-term MACE in advanced-age ACS patients, with HR values of 1.546 (1.049–2.280, p = 0.028) and 1.491 (1.011–2.198, p = 0.044), respectively.Conclusion Elevated UA levels were identified as independent risk factors for MACE in elderly patients with ACS. The optimal predictive value of UA for poor cardiovascular prognosis was significantly lower than the traditional definition of hyperuricemia.